2010
DOI: 10.1128/jvi.02491-09
|View full text |Cite
|
Sign up to set email alerts
|

The 3C Protein of Enterovirus 71 Inhibits Retinoid Acid-Inducible Gene I-Mediated Interferon Regulatory Factor 3 Activation and Type I Interferon Responses

Abstract: Enterovirus 71 (EV71) is a human pathogen that induces hand, foot, and mouth disease and fatal neurological diseases. Immature or impaired immunity is thought to associate with increased morbidity and mortality. In a murine model, EV71 does not facilitate the production of type I interferon (IFN) that plays a critical role in the first-line defense against viral infection. Administration of a neutralizing antibody to IFN-␣/␤ exacerbates the virus-induced disease. However, the molecular events governing this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
233
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(247 citation statements)
references
References 55 publications
13
233
1
Order By: Relevance
“…3C, lanes 5 and 6). These two mutants are abolished for the RNA binding activity but not the protease activity of 3C (15). All of these mutants were expressed at levels comparable to the level wild-type 3C, as determined by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…3C, lanes 5 and 6). These two mutants are abolished for the RNA binding activity but not the protease activity of 3C (15). All of these mutants were expressed at levels comparable to the level wild-type 3C, as determined by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Several studies have suggested that EV71 suppresses antiviral immunity (9,10,(13)(14)(15)(16)(17). In addition to inhibition of type I IFN induction, EV71 has evolved strategies to counter inflammasome activation through cleavage of NLRP3 by viral proteases 2A and 3C (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence assays were done as described (36). For mitochondria staining, cells were incubated for 10 min at 37°C in growth medium containing 200 nM MitoTracker Red CMXRos (Invitrogen), followed by washes with prewarmed PBS buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Lysates were incubated overnight at 4°C with the indicated antibodies, followed by incubation with protein A/G agarose beads (Santa Cruz Biotechnology) for 2 h at 4°C. After four washes with RIPA buffer, immunoprecipitates were subjected to Western blot analysis as described (36).…”
Section: Methodsmentioning
confidence: 99%